The Political Economy of Trans-Related Healthcare: The commodification of Trans-bodies between Medical Knowledge and the Global Market - Vasconcelos, Pedro; Aboim, Sofia (13th Conference of the European Sociological Association - (Un)Making Europe: Capitalism, Solidarities, Subjectivities, 2017)
This paper examines the transnational political economy underpinning the constitution of healthcare regimes addressing gender variance and targeting transgender people. When self-determination is being recognized as a principle for legal gender change, a material analysis of the effects and processes of access to health provisions implies considering three aspects. Firstly, the ways in which maldistribution cohabitates with the recognition of multiple trans identities. Secondly, a transnational perspective is paramount, whether we analyse the uneven access to healthcare or the formation of a ‘class’ of experts (the specialists on transsexual care) that operate in the global market. Thirdly, considering biopower and the relation power-knowledge as market-driven rather than state-driven implies a wider formulation, which intends to expand Foucault’s original contribution on the basis of marketized strategies and the commodification of (trans)bodies. Drawing on qualitative fieldwork with trans-people and healthcare professionals in Portugal and the United Kingdom, we argue that the commodification of health at the global level impacted protocols and standards of care. When rights are being gained and laws privilege self-determination, thereby fostering a regime of self-governance of gender identities, the material support to transgender people decreases with neo-liberal capitalism dominating the offer of care for profit. While the State controls still the bureaucracy of gender identity, the transnational market provides the services to transform the gendered body. Consequently, and along class lines, opportunities for expanding a global market of privatized trans medical care filled the gap, reproducing inequality at the expenses of a political economy for social and gender justice.